The Effect of Education on Food Menu Selection Using Blooket on the Knowledge of Postpartum Mothers - Andin Fadhia Ramadhany; Susanti Pratamaningtyas; Indah Rahmaningtyas; Desy Dwi Cahyani (Jurnal Kebidanan Manna, 2026)
Introduction: Diabetes Mellitus is a metabolic disease closely linked to dietary habits. For postpartum mothers, selecting a healthy and nutritionally balanced diet plays a crucial role in maintaining health and reducing the future risk of developing Diabetes Mellitus. However, limited knowledge regarding appropriate food choices can hinder the adoption of a healthy diet. Health education utilizing the Blooket platform is expected to improve postpartum mothers' knowledge regarding healthy food selection. This study aims to analyze the impact of education on food selection using Blooket on the knowledge of postpartum mothers. Methods: This study employed a pre-experimental design with a one-group pretest-posttest approach. The study population consisted of 36 postpartum mothers in the Sukorame Community Health Center (Puskesmas) area. A total sample of 36 respondents was selected using the total sampling technique. Data were collected via a questionnaire on food selection knowledge and analyzed using the Shapiro-Wilk test and the Wilcoxon Signed Rank Test at a 5% significance level. Results: Prior to the Blooket-based education, the postpartum mothers' knowledge levels fell into the moderate and high categories. Following the intervention, all respondents fell into the high knowledge category. The Wilcoxon Signed Rank Test yielded a Z-value of -5.094 and a p-value of 0.001 (p<0.05), indicating a significant effect of the Blooket-based food selection education on the mothers' knowledge. Discussion: Education using Blooket is effective in enhancing postpartum mothers' knowledge regarding food selection. The presentation of material—concise, systematic, and accompanied by illustrations—facilitated respondent understanding and allowed the content to be reused for independent study. Therefore, Blooket has the potential to serve as an alternative health education tool to improve postpartum mothers' knowledge regarding healthy food choices during the postpartum period.